Rebellion or Revolution? - Cruse, Harold (Book collections on Project MUSE., 2009)
One of the leading writers of African American intellectual life in the second half of the twentieth century, Harold Cruse first came to international attention in 1967 with the publication of his influential and inflammatory book, The Crisis of the Negro Intellectual. This fiercely opinionated and deeply informed critique of both integrationism and black nationalism established Cruse as a bold new voice on race and resistance in America. First published in the wake of The Crisis of the Negro Intellectual's success, Rebellion or Revolution? collects reviews and essays Cruse wrote between 1950 a.